Statistical control of the conilon coffee semi-mechanized harvesting process - Littig, Matheus Nimer; da Vitória, Edney Leandro (Brazilian Journal of Production Engineering, 2021)
Compared to other crops, the conilon coffee harvest is more difficult to execute, due to the shape of the plant, the uneven maturity and the high water contente of the fruits, which impairs the mechanization of the operations. In this way, the harvesting process is the final step of a productive process, and losses must be kept within acceptable standards. The objective of the work was to qualitatively and quantitatively evaluate the time of semi-mechanized harvesting of conilon coffee using statistical process control (CEP). The study took place in the municipality of Pinheiros-ES, where 30 sampling points were sampled from the same plot, selected sequentially at the beginning of the harvest. At each point, the variables times for positioning the tarpaulin, times for stripping over the tarpaulin, time for collecting the tarpaulin, time for positioning the tractor-picker assembly, total time, and maintenance time were evaluated.Both parameters analyzed were out of statistical process control. Bearing in mind that the time for positioning the tarp presentes characteristics or variables that influence the time for distributing the tarp and that the total time of the semi-mechanized harvest does not meet the requiremets of statistical process control.